Separator for non-aqueous electrolyte secondary battery, component for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

The separator for nonaqueous electrolyte secondary batteries, featuring a polyolefin porous film with low molecular chain orientation, addresses the challenge of shock absorption while maintaining ion permeability and mechanical integrity, enhancing battery performance and safety.

JP7653283B2Active Publication Date: 2025-03-28エスエスエルエム株式会社
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021058381
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-03-28
Estimated Expiration
2041-03-30

AI Technical Summary

Technical Problem

Conventional separators for nonaqueous electrolyte secondary batteries lack effective shock absorption while maintaining good ion permeability, tear resistance, and flexibility.

Method used

A separator with a polyolefin porous film that has a low molecular chain orientation, characterized by a peak half-width of 30 degrees or more in the MD direction and a maximum minimum strength ratio of 3.6 or less, enhancing shock absorption without compromising ion permeability and mechanical properties.

Benefits of technology

The proposed separator achieves excellent shock absorption in both the MD and TD directions while maintaining good ion permeability, tear resistance, and flexibility, thereby improving the overall performance and safety of nonaqueous electrolyte secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653283000003
    Figure 0007653283000003
  • Figure 0007653283000004
    Figure 0007653283000004
  • Figure 0007653283000005
    Figure 0007653283000005
Patent Text Reader

Abstract

To provide a non-aqueous electrolyte secondary battery separator that is excellent in shock absorption.SOLUTION: A non-aqueous electrolyte secondary battery separator includes a polyolefin porous film in which a peak half-value width W of an MD direction component calculated from an azimuth angle profile of the scattering peak of a (110) plane obtained by wide-angle X-ray scattering measurement performed by irradiating the surface with X-rays from the vertical direction is 30 degrees or more and / or a maximum-to-minimum intensity ratio r calculated from a Fourier transform azimuthal profile obtained by observing from the surface with SEM is 3.6 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for a nonaqueous electrolyte secondary battery, a member for a nonaqueous electrolyte secondary battery, and a nonaqueous electrolyte secondary battery. [Background technology]

[0002] 2. Description of the Related Art Non-aqueous electrolyte secondary batteries, such as lithium secondary batteries, are currently widely used as batteries for devices such as personal computers, mobile phones and personal digital assistants, or as on-board batteries for vehicles.

[0003] As a separator for such a non-aqueous electrolyte secondary battery, for example, a separator including a porous film containing polyolefin as a main component is known.

[0004] For example, Patent Document 1 describes that a separator containing a porous film that is mainly composed of polyethylene and has a high orientation in the MD direction of the c-axis of the polyethylene crystal has excellent blade sharpness and a low shutdown temperature, and is useful as a separator for a nonaqueous electrolyte secondary battery. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-103044 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the above-mentioned conventional separators have room for improvement in terms of shock absorption properties.

[0007] Therefore, an object of one aspect of the present invention is to provide a separator for a non-aqueous electrolyte secondary battery that has excellent impact absorption properties while maintaining good ion permeability, tear resistance, and flexibility. [Means for solving the problem]

[0008] Conventionally, it has been believed that separators having a high degree of orientation in the MD direction of the c-axis of polyethylene crystals, such as the separator described in Patent Document 1, are more useful as separators for non-aqueous electrolyte secondary batteries.

[0009] However, the present inventors unexpectedly found that a separator containing a porous film containing polyolefin as a main component and in which the molecular chains of the polyolefin have low orientation has excellent impact absorption properties and is useful as a separator for non-aqueous electrolyte secondary batteries, and thus arrived at the present invention.

[0010] An embodiment of the present invention includes the following inventions [1] to [6].

[0011] [1] A separator for a non-aqueous electrolyte secondary battery comprising a polyolefin porous film, The polyolefin porous film satisfies any one or more of the following conditions (1) and (2): (1) The half-width W of the peak in the MD direction component calculated from the azimuth angle profile of the scattering peak of the (110) plane obtained by wide-angle X-ray scattering measurement performed by irradiating the surface of the polyolefin porous film with X-rays from a vertical direction is 30 degrees or more; (Here, the peak half-width W is the width of the peak at the scattering intensity where the peak height is half the peak height when the difference between the maximum scattering intensity of the peak observed in the TD direction in the azimuth angle profile and the minimum scattering intensity of the valley with the lowest intensity adjacent to the peak is defined as the peak height.) (2) The maximum-minimum intensity ratio r calculated from a Fourier transform azimuth angle profile obtained by observing the surface of the polyolefin porous film with a SEM is 3.6 or less.

[0012] (Here, the maximum-minimum intensity ratio r is the maximum value I in the range from 45 degrees to 135 degrees of the Fourier transform azimuth angle profile. max1 and the minimum value I min1, and the maximum value I in the range from 135 degrees to 225 degrees max2 and the minimum value I min2 It is calculated using the following formula (A). r=(I max1 / I min1 +I max2 / I min2 ) / 2(A)) [2] The separator for a nonaqueous electrolyte secondary battery according to [1], wherein the polyolefin porous film satisfies the following (a) to (e): (a) The film thickness is equal to or greater than 5 μm and less than 18 μm; (b) Air permeability (Gurley value) per 13 μm of film thickness is 50 to 200 seconds / 100 cc; (c) MD elongation at break is 20% GL That's it; (d) MD breaking strength is 50-190 MPa; (e) TD elongation at break is 20 to 300% GL It is.

[0013] [3] The separator for a non-aqueous electrolyte secondary battery according to [1] or [2], wherein the polyolefin porous film contains a wax component having a weight average molecular weight of 1,000 to 4,000.

[0014] [4] The electrophotographic imaging device further comprises a porous layer containing a resin, The separator for a non-aqueous electrolyte secondary battery according to any one of [1] to [3], wherein the porous layer is laminated on one side or both sides of the polyolefin porous film.

[0015] [5] A member for a non-aqueous electrolyte secondary battery, comprising a positive electrode, the separator for a non-aqueous electrolyte secondary battery according to any one of [1] to [4], and a negative electrode, arranged in this order.[6]

[0016] [6] A non-aqueous electrolyte secondary battery comprising the separator for a non-aqueous electrolyte secondary battery according to any one of [1] to [4]. Effect of the Invention

[0017] The separator for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention exhibits the effect of having excellent impact absorption properties while maintaining good ion permeability, tear resistance, and flexibility. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a schematic diagram showing a change in the internal structure of a polyolefin porous film constituting a separator for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention when the separator is subjected to an impact. [Diagram 2] FIG. 1 is a diagram showing an example of how to determine the half-width W when the peaks do not overlap in an azimuth angle profile of wide-angle X-ray scattering. [Diagram 3] FIG. 1 is a diagram showing an example of how to determine the half-width W when peaks overlap in an azimuth angle profile of wide-angle X-ray scattering. [Figure 4] FIG. 13 is a diagram showing an example of a method for determining a maximum value and a minimum value used to determine a maximum-minimum intensity ratio r. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each of the configurations described below, and various modifications are possible within the scope of the claims. The technical scope of the present invention also includes embodiments obtained by appropriately combining the technical means disclosed in different embodiments. In this specification, unless otherwise specified, "A to B" representing a numerical range means "A or more, B or less."

[0020] In this specification, the MD direction (machine direction) means the direction in which the sheet-shaped polyolefin resin composition, the primary sheet, the secondary sheet and the porous film are conveyed in the manufacturing method of the porous film described later. The TD direction (transverse direction) means the direction parallel to the surface of the sheet-shaped polyolefin resin composition, the primary sheet, the secondary sheet and the porous film, and perpendicular to the MD direction.

[0021] [Embodiment 1: Separator for non-aqueous electrolyte secondary battery] 1.Separator for non-aqueous electrolyte secondary batteries A separator for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention is a separator for a non-aqueous electrolyte secondary battery comprising a polyolefin porous film, wherein the polyolefin porous film satisfies any one or more of the following conditions (1) and (2): (1) The half-width W of the peak in the MD direction component calculated from the azimuth angle profile of the scattering peak of the (110) plane obtained by wide-angle X-ray scattering measurement performed by irradiating the surface of the polyolefin porous film with X-rays from a vertical direction is 30 degrees or more; (Here, the peak half-width W is the width of the peak at the scattering intensity where the peak height is half the peak height when the difference between the maximum scattering intensity of the peak observed in the TD direction in the azimuth angle profile and the minimum scattering intensity of the valley with the lowest intensity adjacent to the peak is defined as the peak height.) (2) In a Fourier transform azimuth angle profile obtained by observing the surface of the polyolefin porous film with a scanning electron microscope, the maximum-minimum intensity ratio r is 3.6 or less.

[0022] (Here, the maximum-minimum intensity ratio r is 45 Degree From 135 Degree The maximum value in the range of I max1 and the minimum value I min1 , and 135 Degree From 225 DegreeThe maximum value in the range of I max2 and the minimum value I min2 It is calculated using the following formula (A). r=(I max1 / I min1 +I max2 / I min2 ) / 2··(A)) A separator for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention includes a polyolefin porous film. Hereinafter, the polyolefin porous film is also simply referred to as a "porous film".

[0023] The separator for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention may be a separator for a nonaqueous electrolyte secondary battery made of the porous film. Also, the separator for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention may be a laminate including the porous film and a porous layer described later.

[0024] The laminated non-aqueous electrolyte secondary battery separator described below is also referred to as a "laminated non-aqueous electrolyte secondary battery separator".

[0025] Furthermore, the separator for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention may, if necessary, include a known porous layer such as a heat-resistant layer, an adhesive layer, or a protective layer, as another porous layer, in addition to the porous film and the porous layer, as described below.

[0026] [Porous film] The porous film contains polyolefin resin, and generally is a porous film mainly composed of polyolefin resin. "Mainly composed of polyolefin resin" means that the ratio of polyolefin resin in the porous film is 50% by volume or more, preferably 90% by volume or more, more preferably 95% by volume or more of the total material constituting the porous film.

[0027] The porous film has many interconnected pores inside, allowing gas or liquid to pass from one surface to the other.

[0028] In one embodiment of the present invention, the porous film has a peak half-width W of the MD direction component of 30 degrees or more, calculated from the azimuth angle profile of the scattering peak of the (110) plane, and / or a maximum-to-minimum intensity ratio r of 3.6 or less, calculated from a Fourier transform azimuth angle profile obtained by observing the surface with a scanning electron microscope (hereinafter, "SEM").

[0029] [MD component peak half-width W] The peak half-width W of the MD component (hereinafter, "peak half-width W") is a parameter that indicates the degree of disorder in the MD orientation of the polyolefin molecular chains inside the porous film. The polyolefin molecular chains form a dendritic structure that forms the pores inside the porous film. The larger the peak half-width W, the greater the disorder in the orientation, which means that the orientation of the polyolefin molecular chains in the MD is lower.

[0030] In a porous film having a peak half-width W of 30 degrees or more, the molecular chain of the polyolefin has low orientation in the MD direction, so that the dendritic structure has room to extend in the MD direction, as shown in the left diagram of Figure 1.

[0031] When impact energy is applied to the porous film from the outside, the dendritic structure can absorb the impact energy by extending in the MD direction, as shown in the right diagram of Figure 1. When the impact energy is applied in the TD direction, the force that extends the internal structure of the porous film acts more strongly in the MD direction.

[0032] Therefore, the separator for a non-aqueous electrolyte secondary battery including the porous film having the peak half width W of 30 degrees or more according to one embodiment of the present invention has excellent impact absorption properties, particularly excellent impact absorption properties in the TD direction.

[0033] The larger the peak half-width W, the better the impact absorption, and therefore the more preferable. Specifically, the peak half-width W is preferably 40 degrees or more, and more preferably 50 degrees or more. In addition, if the peak half-width W is excessively large, the orientation of the dendritic structure inside the porous film becomes excessively low, and the strength of the porous film itself may decrease. From the viewpoint of optimizing the strength, the peak half-width W is preferably 90 degrees or less, and more preferably 70 degrees or less.

[0034] The peak half-width W can be calculated based on the azimuth angle profile of the scattering peak obtained by wide-angle X-ray scattering measurement. Specifically, the peak half-width W is measured, for example, by the following methods (1), (2), and (3), or (1), (2), and (3').

[0035] (1) The surface of a separator for a non-aqueous electrolyte secondary battery is irradiated with X-rays from a vertical direction, and wide-angle X-ray scattering measurement is performed to obtain a two-dimensional scattering image. The two-dimensional scattering image is corrected using a two-dimensional scattering image (air blank) obtained without placing a measurement sample to obtain a corrected two-dimensional scattering image. "Irradiating the surface with X-rays from a vertical direction" refers to irradiating the surface with X-rays such that the angle between the X-rays irradiated from an X-ray irradiator (for example, NANO-Viewer manufactured by Rigaku Corporation, described later) and the surface (the irradiation angle of the X-rays to the surface) is 90 degrees.

[0036] (2) From the corrected two-dimensional scattering image, the TD direction is 180 with respect to the scattering peak of the 110 plane of the orthorhombic crystal of the polyolefin polymer. Degree The azimuth angle profile is calculated by plotting the azimuth angle β as follows:

[0037] (3) As shown in FIG. 2, in the azimuth angle profile, the difference between the maximum scattering intensity of a peak observed in the TD direction and the minimum scattering intensity of the valley adjacent to the peak and having the lowest intensity is defined as the peak height. The width of the peak at the scattering intensity where the peak height is half is calculated as the half-width W of the MD component.

[0038] (3') As shown in FIG. 3, when one side of a peak observed in the TD direction overlaps with an adjacent peak, the half-width W is calculated as an angle twice the absolute value of the difference between βh and βp, ​​based on the following formula (B), where βh is the azimuth angle of the scattering intensity of the peak at which the peak height is half, and βp is the azimuth angle at which the scattering intensity of the peak is maximum. W = 2 × |βh-βp| (B) The position of the peak observed in the TD direction varies depending on the type of the polyolefin, etc. For example, when the polyolefin is polyethylene, the peak observed in the TD direction is detected at a scattering angle 2θ of 20 degrees to 23 degrees.

[0039] [Maximum-minimum intensity ratio r] The maximum-minimum intensity ratio r is a parameter representing the orientation of the molecular chains of the polyolefin throughout the entire interior of the porous film. The smaller the maximum-minimum intensity ratio r, the lower the orientation of the molecular chains of the polyolefin throughout the entire interior of the porous film.

[0040] In one embodiment of the present invention, the porous film having the maximum-minimum intensity ratio r of 3.6 or less has a low orientation of the molecular chain of polyolefin throughout the entire inside of the porous film, so that the dendritic structure inside the porous film has a margin to extend not only in the MD direction but also in the TD direction.

[0041] Here, when impact energy is applied to the porous film from the outside, the dendritic structure inside the porous film can absorb the impact energy by stretching in the MD and TD directions. Generally, since porous films are easily stretched in the TD direction, it is considered that a porous film having the maximum-minimum strength ratio r of 3.6 or less is easily stretched in the TD direction and can more strongly absorb impact energy in the MD direction.

[0042] Therefore, a separator for a non-aqueous electrolyte secondary battery including a porous film having a maximum-minimum strength ratio r of 3.6 or less has excellent shock absorption properties, particularly in the MD direction.

[0043] The smaller the maximum-minimum intensity ratio r, the better the impact absorption, and therefore the more preferable. Specifically, the maximum-minimum intensity ratio r is preferably 3.2 or less, and more preferably 2.6 or less. In addition, if the maximum-minimum intensity ratio r is excessively small, the orientation of the dendritic structure inside the porous film becomes excessively low, and the strength of the porous film itself may be reduced. From the viewpoint of optimizing the strength of the porous film itself, the maximum-minimum intensity ratio r is preferably 1.0 or more, more preferably 1.5 or more, and particularly preferably 2.0 or more.

[0044] The maximum-minimum intensity ratio r can be calculated based on a Fourier transform azimuth angle profile obtained by observing the surface of the porous film with a SEM. Specifically, the maximum-minimum intensity ratio r is measured, for example, by the following methods (1) to (6).

[0045] (1) The surface of a porous film is subjected to a conductive treatment, and then the surface is observed by SEM so that the MD direction is the horizontal direction of the image, and a secondary electron image of the surface is obtained. The SEM observation is performed in three different fields of view on the surface of the sample (porous film).

[0046] (2) Each of the secondary electron images in the three different fields of view is trimmed to a square of 889 pixels x 889 pixels (17.6 μm square). Then, binarization is performed using Otsu's automatic discrimination method to obtain a binarized image. Next, circular masking is performed on the binarized image by filling in the outside of a circle with the width of the image as a diameter with black, to obtain a masked image.

[0047] (3) Each of the masked images in the three different fields of view is converted into a power spectrum image by two-dimensional Fourier transformation to obtain a power spectrum image in the range corresponding to a period from 0.2 μm to 1 μm. Based on the power spectrum image, an azimuth angle profile is calculated with the TD direction set to 0 degrees.

[0048] (4) From the azimuth angle profiles in three different fields of view, the maximum value I of the azimuth angle profile in the range from 45 degrees to 135 degrees as shown in Figure 4 max1 and the minimum value I min1 , and the maximum value of the azimuth angle profile in the range from 135 degrees to 225 degrees I max2 and the minimum value I min2 get.

[0049] (5) I in three different fields of view max1 , I min1 , I max2 and I min2 Using the above, the maximum / minimum intensity ratio r for each of the three different fields of view is calculated according to the following formula (A). r=(I max1 / I min1 +I max2 / I min2 ) / 2··(A) (6) The average value of each of the maximum and minimum intensity ratios r is calculated, and this is set as the maximum and minimum intensity ratio r.

[0050] The porous film in one embodiment of the present invention can satisfy both the requirement that the peak half-width W of the MD component is 30 degrees or more and the requirement that the maximum-to-minimum intensity ratio r is 3.6 or less. A separator for a nonaqueous electrolyte secondary battery including a porous film that satisfies the above two requirements can more suitably improve the impact absorption in both the TD and MD directions.

[0051] The MD breaking elongation of the porous film is 20% GL (Gauge Length) It is preferable that the MD breaking elongation is 30% GL or more, and more preferably 30% GL or more. The upper limit of the MD breaking elongation is not particularly limited, but it can usually be 300% GL or less. The MD breaking strength of the porous film is preferably 20 to 190 MPa, and more preferably 50 to 150 MPa. The MD breaking elongation and the MD breaking strength are 、J It is measured in accordance with the IS K7127 standard.

[0052] Here, the MD breaking elongation is expressed as a ratio (%) of the length of the porous film elongated in the MD direction when the porous film breaks to the length of the porous film in the MD direction before the operation, when a predetermined operation is performed. The predetermined operation is an operation of elongating the porous film in the MD direction.

[0053] The TD breaking elongation of the porous film is 20 to 300 % G L It is preferable that the concentration is 50 to 250 % G L The TD breaking strength of the porous film is preferably 20 to 190 MPa, and more preferably 50 to 150 MPa. The TD breaking elongation and the TD breaking strength are measured by a method in accordance with JIS K7127 standard.

[0054] The TD breaking elongation of the porous film can be expressed in the same manner as the MD breaking elongation, that is, when the porous film is subjected to an operation of stretching in the TD direction, it is expressed as a ratio (%) of the length of the porous film stretched in the TD direction when the porous film is broken to the length of the porous film in the TD direction before the operation.

[0055] On the other hand, in the case of a sheet-type porous film, i.e., a porous film that has been processed to a specified size, it may be difficult to distinguish between the TD direction and the MD direction. In that case, if the sheet-type porous film is rectangular, the breaking elongation when stretched in a direction parallel to a specific side of the rectangle and the breaking elongation when stretched in a direction perpendicular to the specific side of the rectangle are measured. Since a porous film is usually weaker in strength when stretched in the MD direction, the smaller of the two breaking elongations is taken as the "MD breaking elongation value" and the larger is taken as the "TD breaking elongation value."

[0056] In addition, when the TD direction and MD direction of the porous film cannot be distinguished and the shape of the porous film is not rectangular, the porous film is stretched in a plurality of arbitrary directions, and the breaking elongation when stretched in each direction is measured. Then, the smallest value of each breaking elongation measured is taken as the "MD breaking elongation value". Then, the direction perpendicular to the stretching direction in which the "MD breaking elongation value" is measured is taken as the "TD direction", and the breaking elongation value in that direction is taken as the "TD breaking elongation value". In this specification, the shape of the porous film refers to the shape of the surface perpendicular to the thickness direction.

[0057] The thickness of the porous film is preferably 5 μm or more and less than 18 μm. If the thickness of the porous film is 5 μm or more, an internal short circuit of the battery can be sufficiently prevented. On the other hand, if the thickness of the porous film is less than 18 μm, an increase in size of the nonaqueous electrolyte secondary battery can be prevented.

[0058] When the thickness of the porous film is excessively thick, for example, when the thickness is 18 μm or more, a certain degree of impact resistance can be obtained depending on the thickness, but this configuration cannot meet the recent demand for thinner separators for nonaqueous electrolyte secondary batteries.

[0059] On the other hand, the separator for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention can exhibit sufficient impact absorption even if it has a thickness of, for example, 5 μm or more and less than 18 μm, because the peak half-width W of the MD direction component is 30 degrees or more and / or the maximum-to-minimum intensity ratio r is 3.6 or less.

[0060] The polyolefin resin has a weight average molecular weight of 5×10 5 ~15×10 6 In particular, it is more preferable that the polyolefin resin contains a high molecular weight component having a weight average molecular weight of 1,000,000 or more, since the strength of the resulting porous film and the separator for a non-aqueous electrolyte secondary battery containing the porous film is improved.

[0061] In order to control the peak half-width W of the MD component to 30 degrees or more and / or the maximum-minimum intensity ratio r to 3.6 or less, the main component of the polyolefin resin is preferably a polyolefin having a weight-average molecular weight of 500,000 or more. Here, the term "main component" refers to a component that accounts for 50% by weight or more of the total weight of the polyolefin resin.

[0062] The polyolefin resin is not particularly limited, but examples thereof include homopolymers or copolymers obtained by polymerizing one or more monomers selected from monomers such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, and 1-hexene.

[0063] Examples of the homopolymer include polyethylene, polypropylene, and polybutene, and examples of the copolymer include an ethylene-propylene copolymer.

[0064] Among these, polyethylene is more preferred because it can prevent excessive current from flowing through the separator for non-aqueous electrolyte secondary batteries at a lower temperature. Examples of the polyethylene include low-density polyethylene, high-density polyethylene, linear polyethylene (ethylene-α-olefin copolymer), and ultra-high molecular weight polyethylene having a weight-average molecular weight of 1 million or more. Among these, ultra-high molecular weight polyethylene having a weight-average molecular weight of 1 million or more is more preferred.

[0065] The weight per unit area of ​​the porous film, i.e., the weight per unit area, is usually 4 to 20 g / m2 so as to increase the weight energy density and volume energy density of the battery. 2 is preferably 5 to 12 g / m 2 It is more preferable that:

[0066] The puncture strength of the porous film is preferably 5.0 N or more, more preferably 5.3 N or more, and even more preferably 5.5 N or more. The puncture strength of 5.0 N or more means that the strength of the separator for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention is sufficiently high. Therefore, it is preferable because better shock absorption can be achieved. The puncture strength can be measured by the following method.

[0067] (i) After the porous film is fixed to the upper surface of a table with a washer of 12 mmφ, a pin (pin diameter 1 mmφ, tip 0.5R) is pierced into the porous film at a piercing speed of 10 mm / sec and a piercing depth of 10 mm. Here, the shape and material of the table are not limited as long as the upper surface is flat.

[0068] (ii) The maximum stress (gf) when the pin is pierced into the porous film in (i) is measured, and the measured value is regarded as the piercing strength of the film.

[0069] The porosity of the porous film is preferably 20% by volume to 80% by volume, and more preferably 30% by volume to increase the amount of electrolyte retained and to provide the function of reliably preventing (shutting down) the flow of excessive current at a lower temperature.

[0070] The air permeability (Gurley value) of the porous film per 13 μm of film thickness is preferably 50 to 200 sec·100 cc / 13 μm, and more preferably 50 to 190 sec·100 cc / 13 μm, from the viewpoint of maintaining good ion permeability.

[0071] The pore size of the pores in the porous film is preferably 0.3 μm or less, and more preferably 0.14 μm or less, from the viewpoints of sufficient ion permeability and preventing the intrusion of particles constituting the electrode.

[0072] 2. Manufacturing method of polyolefin porous film The method for producing a polyolefin porous film in one embodiment of the present invention is not particularly limited, but specific examples include a method including steps (A) to (D) shown below, a method including steps (A') to (C'), and a method including steps (A') to (D').

[0073] (A) a polyolefin resin and, optionally, a pore-forming agent etc. A step of adding additives to a kneader and melt-kneading to obtain a polyolefin resin composition; (B) a step of extruding the obtained polyolefin resin composition through a T-die of an extruder, stretching it in a first direction, and forming it into a sheet shape to obtain a primary sheet; (C) stretching the primary sheet in a second direction different from the first direction to obtain a secondary sheet; (D) stretching the secondary sheet in a second direction different from the first direction while shrinking the secondary sheet in the first direction.

[0074] (A') a step of adding a polyolefin resin, and optionally a pore-forming agent and additives to a kneader and melt-kneading the mixture to obtain a polyolefin resin composition; (B') extruding the obtained polyolefin resin composition through a T-die of an extruder to obtain a resin sheet, and then stretching the resin sheet in a first direction by a pair of rolls having a surface temperature set at a temperature of 5 to 20°C above the melting point of the polyolefin resin under a linear pressure of 1.25 to 7 t / m to form the resin sheet into a sheet shape to obtain a primary sheet; (C') a step of stretching the primary sheet in a second direction different from the first direction at a temperature equal to or lower than the melting point of the polyolefin resin to obtain a secondary sheet; (D') A step of shrinking the secondary sheet in the second direction and the first direction at a temperature equal to or lower than the melting point of the polyolefin resin.

[0075] The melting point of the polyolefin resin can be determined from the peak temperature in DSC (differential scanning calorimetry). When multiple peaks are present in DSC, the peak temperature with the largest heat of fusion ΔH (J / g) is taken as the melting point.

[0076] In steps (A) and (A'), the amount of the polyolefin resin used is preferably 6% by weight to 45% by weight, and more preferably 9% by weight to 36% by weight, based on the weight of the resulting polyolefin resin composition being 100% by weight. Also, it is preferable that the weight average molecular weight of the main component of the polyolefin is 500,000 or more.

[0077] The polyolefin resin preferably contains a wax component having a weight average molecular weight of 1000 to 4000. By containing the wax component, the orientation of the molecular chain of the polyolefin in the porous film can be appropriately reduced. The wax component is not particularly limited, but may be, for example, polyethylene wax.

[0078] The first direction is preferably the MD direction, and the second direction is preferably the TD direction.

[0079] The pore-forming agent is not particularly limited, but may be, for example, an inorganic filler or a plasticizer. The inorganic filler is not particularly limited, but may be, for example, an inorganic filler, specifically, calcium carbonate. The plasticizer is not particularly limited, but may be, for example, a low molecular weight hydrocarbon such as liquid paraffin.

[0080] In addition to the pore-forming agent, known additives can be used as desired within the scope of the present invention, such as antioxidants.

[0081] In steps (B) and (B'), the method for obtaining the primary sheet is not particularly limited, and the primary sheet can be produced by a sheet forming method such as inflation processing, calendar processing, T-die extrusion processing, or skiff method.

[0082] For example, the sheet molding temperature in the sheet molding method, such as the T-die extrusion temperature in the T-die extrusion process, is preferably 200°C or higher and 280°C or lower, and more preferably 220°C or higher and 260°C or lower.

[0083] In step (B), a method for obtaining a primary sheet with higher thickness accuracy can be exemplified by a method of roll-molding the polyolefin resin composition using a pair of rotary molding tools adjusted to a surface temperature higher than the melting point of the polyolefin resin contained in the polyolefin resin composition. In this case, the surface temperature of the rotary molding tools is preferably (melting point of polyolefin resin + 5) ° C or higher. The upper limit of the surface temperature is preferably (melting point of polyolefin resin + 30) ° C or lower, and more preferably (melting point of polyolefin resin + 20) ° C or lower.

[0084] The pair of rotary molding tools may be a roll or a belt. The peripheral speeds of both rotary molding tools do not necessarily have to be exactly the same, and the difference between them may be within about ±5%. Also, the primary sheet may be a laminate of single-layer sheets obtained by the sheet forming method.

[0085] When the polyolefin resin composition is roll-molded using a pair of rotary molding tools, the polyolefin resin composition extruded in the form of strands from an extruder may be directly introduced between the pair of rotary molding tools, or a polyolefin resin composition that has been pelletized may be used.

[0086] The stretching ratio in step (B) is preferably 1.1 to 1.9, more preferably 1.2 to 1.8. The stretching temperature in step (B) is preferably 120° C. to 160° C., more preferably 130° C. to 155° C.

[0087] The stretching ratio in step (B') is preferably 4 to 15 times, more preferably 5 to 10. The stretching temperature in step (B') is preferably 120°C to 160°C, more preferably 130°C to 155°C.

[0088] In steps (B) and (B'), the polyolefin resin composition can be cooled by contacting it with a coolant such as cold air or cooling water, or by contacting it with a cooling roll. The method of contacting it with a cooling roll is preferred.

[0089] The first direction in steps (B) and (B') is preferably the MD direction. In step (B), the first direction being the MD direction is preferable because the strength against elongation in the MD direction of the porous film, which is usually the lowest, can be improved by the relaxation operation described later, and the strength against elongation of the entire porous film can be efficiently improved.

[0090] When the polyolefin resin composition and the primary sheet contain a pore-forming agent, the method includes a step of washing the stretched sheet with a washing liquid to remove the pore-forming agent between steps (B) and (C) or after step (C), or between steps (B') and (C') or after step (C').

[0091] The cleaning liquid is not particularly limited as long as it is a solvent capable of removing the pore-forming agent, and examples thereof include an aqueous hydrochloric acid solution, heptane, and dichloromethane.

[0092] The stretching temperature during stretching in the second direction in step (C) is preferably 80°C or higher and 140°C or lower, and more preferably 90°C or higher and 135°C or lower.

[0093] In steps (C) and (C'), the stretching ratio when stretching in the second direction is preferably 2 times or more and 12 times or less, and more preferably 3 times or more and 10 times or less.

[0094] In steps (D) and (D'), the step of starting the stretching of the secondary sheet in the second direction and the step of shrinking the secondary sheet in the first direction may be performed simultaneously, or one may be performed first and then the other. However, it is preferable to perform the steps simultaneously, or to perform the step of starting the stretching of the secondary sheet in the second direction first. In this case, by stretching the secondary sheet in the second direction, a shrinkage force in the first direction acts on the secondary sheet, so that the secondary sheet can be shrunk without wrinkles.

[0095] In steps (D) and (D'), the stretching temperature when the secondary sheet is shrunk in the first direction is preferably 80° C. or more and 140° C. or less, and more preferably 90° C. or more and 130° C. or less. The shrinkage percentage when the secondary sheet is shrunk in the first direction is preferably 10% or more and 50% or less, and more preferably 20% or more and 40% or less.

[0096] In steps (D) and (D'), the stretching ratio when the secondary sheet is stretched in the second direction is preferably 1.2 times or more and 2 times or less, and more preferably 1.3 times or more and 1.5 times or less.

[0097] In steps (D) and (D'), the secondary sheet is shrunk in the first direction, thereby returning the polyolefin molecular chains that were fully stretched during rolling to their original, unstretched state, thereby favorably reducing the orientation of the polyolefin molecular chains in the porous film.

[0098] In addition, it is preferable that the stretching ratio at which the secondary sheet is stretched in the second direction in step (D) is as small as possible compared to the stretching ratio at which the primary sheet is stretched in the second direction in step (C). For example, it is preferable to control the stretching ratio in step (D) to a level at which no wrinkles are generated in the resulting porous film. This makes it possible to more suitably reduce the orientation of polyolefin molecular chains in the resulting porous film.

[0099] In step (B'), the rolling is performed at a temperature of 5 to 20°C above the melting point of the polyolefin resin, and at a linear pressure of 1.25 to 7 t / m, preferably 1.25 to 6 t / m. The linear pressure range is lower than the general linear pressure applied when stretching a resin sheet in the production of a porous film. Thus, the molecular chains of the polyolefin are not fully extended during rolling. This makes it possible to suitably reduce the orientation of the molecular chains of the polyolefin in the resulting porous film.

[0100] As described above, by the method including steps (A) to (D), the method including steps (A') to (C'), and the method including steps (A') to (D'), it is possible to produce a porous film in which the peak half-width W of the MD direction component is 30 degrees or more and / or the maximum-to-minimum intensity ratio r is 3.6 or less.

[0101] 3.Porous layer A separator for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention may be a laminate separator for a non-aqueous electrolyte secondary battery including the polyolefin porous film and a porous layer laminated on one or both sides of the polyolefin porous film.

[0102] The porous layer is a resin layer containing a resin, and is preferably a heat-resistant layer or an adhesive layer. The resin constituting the porous layer is preferably insoluble in the electrolyte of the battery and is electrochemically stable within the range of use of the battery.

[0103] When the porous layer is laminated on one side, the porous layer is preferably laminated on the side of the polyolefin porous film that faces the positive electrode when the film is made into a nonaqueous electrolyte secondary battery, and more preferably on the side that contacts the positive electrode.

[0104] Examples of the resin include polyolefins, (meth)acrylate resins, fluorine-containing resins, polyamide resins, polyimide resins, polyester resins, rubbers, resins having a melting point or glass transition temperature of 180° C. or higher, water-soluble polymers, polycarbonate, polyacetal, and polyether ether ketone.

[0105] Of the above-mentioned resins, polyolefins, (meth)acrylate resins, fluorine-containing resins, polyamide resins, polyester resins and water-soluble polymers are preferred.

[0106] As the polyolefin, polyethylene, polypropylene, polybutene, ethylene-propylene copolymer, and the like are preferable.

[0107] Examples of fluorine-containing resins include polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trichloroethylene copolymer, vinylidene fluoride-vinyl fluoride copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, ethylene-tetrafluoroethylene copolymer, and the like, as well as fluorine-containing rubbers having a glass transition temperature of 23° C. or lower among the above-mentioned fluorine-containing resins.

[0108] As the polyamide-based resin, aramid resins such as aromatic polyamides and wholly aromatic polyamides are preferred.

[0109] Specific examples of the aramid resin include poly(paraphenylene terephthalamide), poly(metaphenylene isophthalamide), poly(parabenzamide), poly(metabenzamide), poly(4,4'-benzanilide terephthalamide), poly(paraphenylene-4,4'-biphenylenedicarboxylic acid amide), poly(metaphenylene-4,4'-biphenylenedicarboxylic acid amide), poly(paraphenylene-2,6-naphthalenedicarboxylic acid amide), poly(metaphenylene-2,6-naphthalenedicarboxylic acid amide), poly(para ... Examples of the poly(4,4'-diphenylsulfonyl terephthalamide) include poly(2-chloroparaphenylene terephthalamide), paraphenylene terephthalamide / 2,6-dichloroparaphenylene terephthalamide copolymer, metaphenylene terephthalamide / 2,6-dichloroparaphenylene terephthalamide copolymer, poly(4,4'-diphenylsulfonyl terephthalamide), paraphenylene terephthalamide / 4,4'-diphenylsulfonyl terephthalamide copolymer, etc. Among these, poly(paraphenylene terephthalamide) is more preferred.

[0110] The resin may be used alone or in combination of two or more kinds.

[0111] The porous layer may contain fine particles. In this specification, the fine particles refer to organic fine particles or inorganic fine particles generally called filler. The fine particles are preferably insulating fine particles.

[0112] The organic fine particles include fine particles made of resin. The inorganic fine particles include fillers made of inorganic substances such as calcium carbonate, talc, clay, kaolin, silica, hydrotalcite, diatomaceous earth, magnesium carbonate, barium carbonate, calcium sulfate, magnesium sulfate, barium sulfate, aluminum hydroxide, boehmite, magnesium hydroxide, calcium oxide, magnesium oxide, titanium oxide, titanium nitride, alumina (aluminum oxide), aluminum nitride, mica, zeolite, and glass. The fine particles may be used alone or in combination of two or more kinds.

[0113] The content of the fine particles in the porous layer is preferably 1 to 99% by volume, and more preferably 5 to 95% by volume, of the porous layer.

[0114] The thickness of the porous layer is preferably 0.5 to 15 μm per layer, more preferably 1 to 10 μm. If the thickness of the porous layer is 0.5 μm or more per layer, internal short circuit due to damage to the nonaqueous electrolyte secondary battery can be sufficiently suppressed. In addition, the amount of electrolyte held in the porous layer becomes sufficient. On the other hand, if the thickness of the porous layer is 15 μm or less per layer, deterioration of rate characteristics or cycle characteristics can be suppressed.

[0115] The weight per unit area of ​​the porous layer, i.e., the basis weight per layer, is 0.33 to 10 g / m 2 It is preferable that the thickness is 0.7 to 7 g / m 2 It is more preferable that:

[0116] The porosity of the porous layer is preferably 20 to 90% by volume, more preferably 30 to 80% by volume, so that sufficient ion permeability can be obtained. Also, the pore size of the pores in the porous layer is preferably 3 μm or less, more preferably 1 μm or less, so that sufficient ion permeability can be obtained in the laminated separator for nonaqueous electrolyte secondary batteries.

[0117] The thickness of the laminated separator for a non-aqueous electrolyte secondary battery is preferably 5.5 μm to 45 μm, and more preferably 6 μm to 25 μm.

[0118] The laminated separator for a non-aqueous electrolyte secondary battery has an air permeability of 100 to 350 in terms of Gurley value. seconds / 100 cc It is preferable that the ratio is 100 to 300. seconds / 100 cc It is more preferable that:

[0119] The puncture strength of the laminate separator for a nonaqueous electrolyte secondary battery is preferably 2.5 N or more, more preferably 3.0 N or more, and even more preferably 3.5 N or more. The puncture strength is measured by the same method as for the porous film.

[0120] The separator for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention may include another porous layer other than the porous film and the porous layer, if necessary, within a range that does not impair the object of the present invention. Examples of the other porous layer include known porous layers such as a heat-resistant layer, an adhesive layer, and a protective layer.

[0121] 4. Method for manufacturing porous layer and laminated separator for non-aqueous electrolyte secondary battery As a method for producing the porous layer in one embodiment of the present invention and the laminated separator for a non-aqueous electrolyte secondary battery in one embodiment of the present invention, for example, a method in which a coating liquid containing the resin contained in the porous layer is applied to one or both sides of the porous film and dried to precipitate a porous layer can be mentioned.

[0122] The coating liquid contains the resin contained in the porous layer. The coating liquid may also contain the fine particles described below that may be contained in the porous layer. The coating liquid may usually be prepared by dissolving the resin that may be contained in the porous layer in a solvent and dispersing the fine particles. Here, the solvent that dissolves the resin is not particularly limited and also serves as a dispersion medium that disperses the fine particles. The resin may also be made into an emulsion by the solvent.

[0123] The coating liquid may be formed by any method as long as it satisfies the conditions, such as the resin solid content (resin concentration) and the amount of fine particles, required to obtain a desired porous layer.

[0124] The method of applying the coating liquid to the porous film is not particularly limited. As the application method, a conventionally known method can be adopted, and specific examples thereof include a gravure coater method, a dip coater method, a bar coater method, and a die coater method.

[0125] [Embodiment 2: Nonaqueous electrolyte secondary battery member, Embodiment 3: Nonaqueous electrolyte secondary battery] The member for a nonaqueous electrolyte secondary battery according to the second embodiment of the present invention comprises a positive electrode, the separator for a nonaqueous electrolyte secondary battery according to the first embodiment of the present invention, and a negative electrode arranged in this order.

[0126] The nonaqueous electrolyte secondary battery according to the third embodiment of the present invention includes the separator for nonaqueous electrolyte secondary batteries according to the first embodiment of the present invention.

[0127] The nonaqueous electrolyte secondary battery is, for example, a nonaqueous secondary battery that obtains electromotive force by doping and dedoping lithium, and may include a nonaqueous electrolyte secondary battery member in which a positive electrode, the nonaqueous electrolyte secondary battery separator, and a negative electrode are laminated in this order. Note that the components of the nonaqueous electrolyte secondary battery other than the nonaqueous electrolyte secondary battery separator are not limited to the components described below.

[0128] The non-aqueous electrolyte secondary battery generally has a structure in which a battery element in which a negative electrode and a positive electrode are opposed to each other via the separator for the non-aqueous electrolyte secondary battery and an electrolyte is impregnated in the structure is sealed in an exterior material. The non-aqueous electrolyte secondary battery is preferably a lithium secondary battery. The term "doping" refers to occlusion, support, adsorption, or insertion, and refers to a phenomenon in which lithium ions enter the active material of an electrode such as a positive electrode.

[0129] The nonaqueous electrolyte secondary battery member includes the separator for a nonaqueous electrolyte secondary battery, and therefore has an effect of enabling the manufacture of a nonaqueous electrolyte secondary battery that is excellent in safety, for example, safety against external impact.

[0130] The nonaqueous electrolyte secondary battery includes the separator for a nonaqueous electrolyte secondary battery, and therefore the nonaqueous electrolyte secondary battery has an effect of being excellent in safety, for example, safety against external impact.

[0131] 1. Positive electrode The nonaqueous electrolyte secondary battery member and the positive electrode in the nonaqueous electrolyte secondary battery are not particularly limited as long as they are generally used as positive electrodes in nonaqueous electrolyte secondary batteries, but for example, a positive electrode sheet having a structure in which an active material layer containing a positive electrode active material and a binder is formed on a current collector can be used. The active material layer may further contain a conductive agent.

[0132] The positive electrode active material may be, for example, a material capable of doping and dedoping lithium ions, specifically, a lithium composite oxide containing at least one transition metal such as V, Mn, Fe, Co, or Ni.

[0133] Examples of the conductive agent include carbonaceous materials such as natural graphite, artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fibers, and organic polymer compound sintered bodies. The conductive agent may be used alone or in combination of two or more kinds.

[0134] Examples of the binder include fluorine-based resins such as polyvinylidene fluoride, acrylic resins, and styrene-butadiene rubber. The binder also functions as a thickener.

[0135] Examples of the positive electrode current collector include conductors such as Al, Ni, stainless steel, etc. Among them, Al is more preferable because it is easy to process into a thin film and is inexpensive.

[0136] Examples of methods for producing a sheet-shaped positive electrode include a method of pressurizing and molding a positive electrode active material, a conductive agent, and a binder on a positive electrode current collector; a method of forming a paste of a positive electrode active material, a conductive agent, and a binder using an appropriate organic solvent, applying the paste to a positive electrode current collector, drying the paste, and then pressing the paste to adhere it to the positive electrode current collector; and the like.

[0137] 2.Negative electrode The nonaqueous electrolyte secondary battery member and the negative electrode in the nonaqueous electrolyte secondary battery are not particularly limited as long as they are generally used as negative electrodes in nonaqueous electrolyte secondary batteries, but for example, a negative electrode sheet having a structure in which an active material layer containing a negative electrode active material and a binder is formed on a current collector can be used. The active material layer may further contain a conductive agent.

[0138] Examples of the negative electrode active material include materials capable of doping and dedoping lithium ions, lithium metal, lithium alloys, etc. Examples of the material include carbonaceous materials, etc. Examples of the carbonaceous materials include natural graphite, artificial graphite, cokes, carbon black, and pyrolytic carbons, etc.

[0139] The negative electrode current collector may be made of, for example, Cu, Ni, stainless steel, etc., and Cu is particularly preferred in lithium secondary batteries because it is difficult to form an alloy with lithium and it is easy to process into a thin film.

[0140] Examples of methods for producing a sheet-shaped negative electrode include a method of pressurizing a negative electrode active material on a negative electrode current collector, a method of forming a paste of a negative electrode active material using an appropriate organic solvent, applying the paste to a negative electrode current collector, drying, and then pressing to fix the paste to the negative electrode current collector, etc. The paste preferably contains the conductive agent and the binder.

[0141] 3.Nonaqueous electrolyte The nonaqueous electrolyte in the nonaqueous electrolyte secondary battery is not particularly limited as long as it is a nonaqueous electrolyte generally used in nonaqueous electrolyte secondary batteries, and for example, a nonaqueous electrolyte obtained by dissolving a lithium salt in an organic solvent can be used. Examples of lithium salts include LiClO4, LiPF6, LiAsF6, LiSbF6, LiBF4, LiCF3SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, Li2B 10 Cl 10 , lithium salts of lower aliphatic carboxylates, LiAlCl4, etc. The lithium salts may be used alone or in combination of two or more.

[0142] Examples of the organic solvent constituting the nonaqueous electrolyte include carbonates, ethers, esters, nitriles, amides, carbamates, sulfur-containing compounds, and fluorine-containing organic solvents obtained by introducing a fluorine group into these organic solvents. The organic solvents may be used alone or in combination of two or more. EXAMPLES

[0143] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0144] [Measurement method] Nonaqueous electrolyte secondary batteries manufactured in Examples 1 to 4 and Comparative Examples 1 to 3 For use The physical properties of the porous film were measured using the following methods.

[0145] [Film thickness] The film thickness (μm) of the separator for the non-aqueous electrolyte secondary battery was measured using a high-precision digital length measuring machine (VL-50) manufactured by Mitutoyo Corporation.

[0146] [Weight per unit area] A sample of 6.4 cm × 4 cm was cut out from the separator for the nonaqueous electrolyte secondary battery, and the weight W (g) of this sample was measured. Next, the weight per unit area (g / m2) of the separator for the nonaqueous electrolyte secondary battery was calculated based on the following formula (C). 2 ) was calculated. Weight per unit area = W / (0.064 × 0.04) (C) [Air permeability] A sample of 60 mm x 60 mm was cut out from the separator for non-aqueous electrolyte secondary batteries. The air permeability of the sample was measured in accordance with JIS P8117. The measured air permeability was then converted into an air permeability equivalent to a thickness of 13 μm. Specifically, when the measured air permeability value was a and the thickness of the sample was b μm, the air permeability equivalent to a thickness of 13 μm was calculated based on the following formula (D). Air permeability converted to a film thickness of 13 μm = a × (13 / b) (D) [Puncture strength] The puncture strength of the separator for non-aqueous electrolyte secondary batteries was measured by the method shown in the section "1. Separator for non-aqueous electrolyte secondary batteries". The measured puncture strength value was then converted into a puncture strength equivalent to a film thickness of 13 μm. Specifically, when the measured puncture strength value is c and the film thickness of the sample used for the puncture strength measurement is d μm, the puncture strength equivalent to a film thickness of 13 μm is calculated based on the following formula (E): Piercing strength was calculated. Puncture strength converted to a film thickness of 13 μm = c × (13 / d) (E) [Breaking elongation, breaking strength] The breaking elongation and breaking strength of the separator for a non-aqueous electrolyte secondary battery were measured by a method conforming to JIS K7127 standard. The specific measuring method is shown below.

[0147] The separator for non-aqueous electrolyte secondary batteries was punched out with a JIS K6251-3 dumbbell (gauge length 20 mm, width 5 mm) so that the MD direction was the longitudinal direction to prepare a measurement sample. The sample was stretched in the MD direction, and the breaking strength and breaking elongation were measured when the separator for non-aqueous electrolyte secondary batteries broke. The average values ​​of the two values ​​obtained by measuring twice were taken as the MD breaking strength and MD breaking elongation.

[0148] In measuring the TD breaking strength and TD breaking elongation, the separator for non-aqueous electrolyte secondary battery was punched out with a JIS K6251-3 dumbbell so that the TD direction was the longitudinal direction to obtain a measurement sample, and the sample was elongated in the TD direction. Except for this, the TD breaking strength and TD breaking elongation were measured in the same manner as the MD breaking strength and MD breaking elongation.

[0149] [Charpy test: measurement of impact absorption energy] Ten rectangular samples of 80 mm x 10 mm with the MD direction as the longitudinal direction were cut out from the separator for non-aqueous electrolyte secondary batteries. The Charpy test was performed in accordance with JIS K7111-1 (2012). The average value of 10 points obtained by 10 measurements was divided by the basis weight of the sample to obtain the impact absorption energy in the MD direction. The basis weight of the sample was the weight of the separator for non-aqueous electrolyte secondary batteries.

[0150] The Charpy test was carried out in the same manner as in the case of the MD direction being the longitudinal direction, except that 10 rectangular samples of 80 mm x 10 mm were cut out with the TD direction being the longitudinal direction. The average of the 10 values ​​obtained from 10 measurements was divided by the basis weight of the sample to obtain the impact absorption energy in the TD direction.

[0151] [MD component peak half-width W] Wide-angle X-ray scattering measurement of the separator (porous film) for non-aqueous electrolyte secondary battery was performed under the conditions shown below, and the peak half-width W of the MD direction component was calculated by the method shown in the section "1. Separator for non-aqueous electrolyte secondary battery". The polyolefin constituting the porous film described in Examples 1 to 3 and Comparative Examples 1 to 3 was polyethylene. Therefore, the scattering peak of the 110 plane of the orthorhombic crystal of the polyethylene polymer was detected at a scattering angle 2θ of 20 degrees to 23 degrees. - Model: Rigaku Nano Viewer ·Tube: Cu-Kα Voltage: 40kV ·Current: 20mA Beam diameter: 0.25mmφ Detector: PILATUS 100k [Maximum-minimum intensity ratio r] The non-aqueous electrolyte secondary battery separator (porous film) was observed by SEM under the conditions shown below, and the maximum-minimum intensity ratio r was calculated by the method shown in the above section "1. Non-aqueous electrolyte secondary battery separator." Acceleration voltage: 2kV ·Magnification: 5000x [Example 1] 70% by weight of ultra-high molecular weight polyethylene powder (GUR4032, manufactured by Ticona) and 30% by weight of polyethylene wax (FNP-0115, manufactured by Nippon Seiro) with a weight average molecular weight of 1000 were prepared. The total of the ultra-high molecular weight polyethylene and the polyethylene wax was 100 parts by weight, and 0.4 parts by weight of an antioxidant (SONGNOX 1010, manufactured by Songwon Industrial Co., Ltd.), 0.1 parts by weight of an antioxidant (IRGAFOS 168, manufactured by BASF Co., Ltd.), and 1.3 parts by weight of sodium stearate were added.

[0152] Furthermore, calcium carbonate having an average particle size of 0.1 μm (manufactured by Maruo Calcium Co., Ltd.) was added so that the amount was 38% by volume relative to the total volume of the obtained mixture. These were mixed in powder form in a Henschel mixer, and then melt-kneaded in a twin-screw kneader to obtain a polyolefin resin composition.

[0153] The polyolefin resin composition was extruded by a single screw extruder to form a resin sheet, rolled by a pair of rolls with a surface temperature set at 147°C at a linear pressure of about 5t / m, and then stretched 4.8 times in the MD direction at a temperature equal to or higher than the melting point of the ultra-high molecular weight polyethylene powder to produce a sheet-like polyolefin resin composition. The obtained sheet-like polyolefin resin composition was immersed in an aqueous hydrochloric acid solution (hydrochloric acid 4 mol / L, nonionic surfactant 0.5 wt%) to remove the calcium carbonate, thereby obtaining a primary sheet. Here, the melting point of the ultra-high molecular weight polyethylene powder used in Example 1 was 135°C.

[0154] Then, both ends of the obtained primary sheet in the TD direction were held by a plurality of holding members adjacent in the MD direction. Then, the primary sheet was stretched in the TD at a stretch ratio of 7.05 times, and the stretched film was subjected to a heat setting treatment at a temperature of 122°C for 0.3 minutes. In this way, a separator for a non-aqueous electrolyte secondary battery was obtained.

[0155] [Example 2] The roll surface temperature during the preparation of the resin sheet was changed to 151° C. A separator for a non-aqueous electrolyte secondary battery was obtained in the same manner as in Example 1 except for this.

[0156] [Example 3] The composition of the polyolefin resin composition was changed to 70% by weight of ultra-high molecular weight polyethylene powder (Decamylene, manufactured by Tosoh Corporation) and 30% by weight of polyethylene wax having a weight average molecular weight of 2000 (Excelex 20700, manufactured by Mitsui Chemicals, Inc.). In addition, calcium carbonate was changed to calcium carbonate having an average particle size of 0.07 μm (manufactured by Maruo Calcium Co., Ltd.). A separator for a non-aqueous electrolyte secondary battery was obtained by the same procedure as in Example 2 except for the above. The melting point of the ultra-high molecular weight polyethylene powder used in Example 3 was 136° C.

[0157] [Example 4] In the same manner as in Example 3, a polyolefin resin composition was obtained.

[0158] The polyolefin resin composition was extruded by a single screw extruder to form a resin sheet, and rolled with a pair of rolls whose surface temperature was set at 151° C. at a linear pressure of about 22 t / m to prepare a sheet-like polyolefin resin composition. The obtained sheet-like polyolefin resin composition was immersed in an aqueous hydrochloric acid solution (hydrochloric acid 4 mol / L, nonionic surfactant 0.5 wt %) to remove the calcium carbonate, thereby obtaining a primary sheet.

[0159] Then, both ends of the obtained primary sheet in the TD direction were held by a plurality of holding members adjacent in the MD direction. The primary sheet was stretched in the TD direction at a stretch ratio of 3.57 times to obtain a secondary sheet.

[0160] Then, both ends of the secondary sheet in the TD direction were held by a plurality of gripping members adjacent in the MD direction. Then, the secondary sheet was stretched in the TD direction at a temperature of 115°C at a stretch ratio of 1.4 times by widening the distance between the gripping members facing each other in the TD direction while relaxing in the MD direction by narrowing the distance between the gripping members adjacent in the MD direction, and the stretched film was heat-set at a temperature of 130°C for 0.5 minutes. In this way, a separator for a non-aqueous electrolyte secondary battery was obtained. The MD relaxation rate at this time was 25%.

[0161] The "MD relaxation rate" refers to the rate of decrease in the length of the porous film in the MD direction relative to the length of the secondary sheet in the MD direction before stretching.

[0162] [Comparative Example 1] In the same manner as in Example 1, a polyolefin resin composition was obtained.

[0163] The polyolefin resin composition was extruded by a single screw extruder to form a resin sheet, and rolled with a pair of rolls whose surface temperature was set at 149° C. at a linear pressure of about 22 t / m to prepare a sheet-like polyolefin resin composition. The obtained sheet-like polyolefin resin composition was immersed in an aqueous hydrochloric acid solution (hydrochloric acid 4 mol / L, nonionic surfactant 0.5 wt %) to remove the calcium carbonate, thereby obtaining a primary sheet.

[0164] Then, both ends of the obtained primary sheet in the TD direction were held by a plurality of holding members adjacent in the MD direction. Then, the primary sheet was stretched in the TD at a stretch ratio of 7.05 times, and the stretched film was subjected to a heat setting treatment at a temperature of 123°C for 0.3 minutes. In this way, a separator for a non-aqueous electrolyte secondary battery was obtained.

[0165] [Comparative Example 2] A separator for a non-aqueous electrolyte secondary battery was obtained by the same method as in Example 2 of Japanese Patent No. 6647418.

[0166] [Comparative Example 3] Commercially available dry separators (Celg a A separator made by RD Co., Ltd. was used as a separator for a non-aqueous electrolyte secondary battery.

[0167] [result] The physical properties of the obtained separator for a non-aqueous electrolyte secondary battery were measured by the above-mentioned methods, and the results are shown in Tables 1 and 2.

[0168] [Table 1]

[0169] [Table 2]

[0170] As shown in Table 2, it can be seen that the separators for nonaqueous electrolyte secondary batteries of Examples 1 to 4 are superior in shock absorption properties to the separators for nonaqueous electrolyte secondary batteries of Comparative Examples 1 to 3.

[0171] Therefore, it was found that the separator for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention has excellent impact absorption properties because the peak half-width W of the MD direction component is 30 degrees or more and / or the maximum-to-minimum intensity ratio r is 3.6 or less. [Industrial Applicability]

[0172] One aspect of the present invention can be suitably used in the manufacture of a non-aqueous electrolyte secondary battery.

Claims

1. A separator for a non-aqueous electrolyte secondary battery comprising a polyolefin porous film, A separator for a non-aqueous electrolyte secondary battery, wherein the polyolefin porous film satisfies any one or more of the following conditions (1) and (2): (1) The half-width W of the peak in the MD direction component calculated from the azimuth angle profile of the scattering peak of the (110) plane obtained by wide-angle X-ray scattering measurement performed by irradiating the surface of the polyolefin porous film with X-rays from a vertical direction is 30 degrees or more; (Here, the peak half-width W is the width of the peak at the scattering intensity where the peak height is half the peak height when the difference between the maximum scattering intensity of the peak observed in the TD direction in the azimuth angle profile and the minimum scattering intensity of the valley adjacent to the peak and having the lowest intensity is defined as the peak height.) (2) The maximum-minimum intensity ratio r calculated from a Fourier transform azimuth angle profile obtained by observing the surface of the polyolefin porous film with a scanning electron microscope is 3.6 or less. (Here, the maximum-minimum intensity ratio r is the maximum value I in the range from 45 degrees to 135 degrees of the Fourier transform azimuth angle profile. max1 and the minimum value I min1 , and the maximum value I in the range from 135 degrees to 225 degrees max2 and the minimum value I min2 It is calculated by the following formula (A) using the above. r=(I max1 / I min1 +I max2 / I min2 ) / 2・・(A))

2. The separator for a non-aqueous electrolyte secondary battery according to claim 1, wherein the polyolefin porous film satisfies the following (a) to (e): (a) the membrane thickness is 5 μm or more and less than 18 μm; (b) the air permeability (Gurley value) per 13 μm of film thickness is 50 to 200 seconds / 100 cc; (c) the MD breaking elongation is 20% GL or more; (d) the MD breaking strength is 50 to 190 MPa; (e) The TD breaking elongation is 20 to 300% GL.

3. 3. The separator for a non-aqueous electrolyte secondary battery according to claim 1, wherein the polyolefin porous film contains a wax component having a weight average molecular weight of 1,000 to 4,000.

4. Further comprising a porous layer containing a resin, 4. The separator for a non-aqueous electrolyte secondary battery according to claim 1, wherein the porous layer is laminated on one or both sides of the polyolefin porous film.

5. A separator for a non-aqueous electrolyte secondary battery as described in claim 4, wherein the resin is an aramid resin.

6. A member for a non-aqueous electrolyte secondary battery, comprising a positive electrode, the separator for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5, and a negative electrode, arranged in this order.

7. A non-aqueous electrolyte secondary battery comprising the separator for non-aqueous electrolyte secondary batteries according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Separator for non-aqueous electrolyte secondary battery, laminated separator for non-aqueous electrolyte secondary battery, member for non-aqueous electrolyte secondary batter, non-aqueous electrolyte secondary battery and porous film manufacturing method

    JP2017103044A

  • Separator for non-aqueous electrolyte secondary battery, laminated separator for non-aqueous electrolyte secondary battery, member for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

    JP2017103045A

  • Polyolefin microporous membrane, separator film for power storage device, and power storage device

    JP2017141428A

  • Separator for nonaqueous electrolyte secondary battery

    JP2018147688A

  • Separator for nonaqueous electrolyte secondary battery

    JP2018147692A